Impact of Subclinical Ketosis on Mastitis and Milk Parameters in Early Lactation Brown Swiss Cows - Payano, IU; Ninahuanca, J; Eulogio , CQ; Gomez, EA; Alonso , LB; Guillen , MF; Fermín, JU; Condor, WG (Journal of the Hellenic Veterinary Medical Society, 2025)
The objective of this study was to determine beta-hydroxybutyrate (BHB) levels as an identifier of subclinical ketosis and its effect on milk parameters and mastitis in postpartum dairy cows raised under highland conditions. A total of 32 primiparous and 32 multiparous cows were evaluated to determine the proportion of cows with subclinical ketosis using a semi-quantitative milk test, as well as the presence of mastitis, glucose levels, body condition, milk yield, and milk parameters such as somatic cell count, milk fat, and protein content. Data were analyzed using ANOVA and contingency tests for categorical variables. The prevalence of subclinical ketosis was 56% in multiparous cows and 14% in primiparous cows. Subclinical ketosis significantly affected (p < 0.05) milk protein reduction, increased somatic cell counts, and higher milk fat content. Cows with subclinical ketosis showed subclinical mastitis rates of 9.3% in primiparous cows and 17% in multiparous cows. Glucose levels were significantly reduced (p < 0.05) in cows with ketosis, with a greater reduction observed in multiparous cows. Body condition scores were lower in cows with subclinical ketosis, especially during early lactation (p < 0.05). Conversely, milk production increased in cows with subclinical ketosis, particularly after the second week postpartum. The findings suggest a potential effect of beta-hydroxybutyrate concentrations on the occurrence of mastitis and certain milk parameters in Brown Swiss cows raised at high altitudes.